Severe pertussis disease in a paediatric population: The role of age, vaccination status and prematurity. (9th June 2022) - Guarnieri, Valentina; Giovannini, Mattia; Lodi, Lorenzo; Astorino, Valeria; Pisano, Laura; Di Cicco, Elisa; Canessa, Clementina; Citera, Francesco; Peroni, Diego; Azzari, Chiara; Ricci, Silvia
Abstract: Aim: To estimate hospitalisation rate and investigate the role of age, prematurity and vaccination status in severe pertussis cases. Methods: We retrospectively evaluated 200 children aged 0–14 years, admitted to the emergency rooms of Meyer Hospital of Florence and Pisa Hospital with a diagnosis of pertussis from 1 October 2010 to 31 January 2020. Results: Children younger than 12 months were 63.0%. Preterm infants were 6.5%. The rate of hospitalisation was 49.0%. Among hospitalised cases, 80.6% were younger than 5 months. Overall, 62.0% were unvaccinated; this percentage increased among hospitalised (73.5%) and preterm subsamples (76.9%). Delays in pertussis vaccination were found in 57.7% of term infants and in 80.0% of preterms. Multivariable analysis confirmed the age under 2 months as the variable at higher risk for hospitalisation (OR 4.49, 95% CI 1.85–10.96, p < 0.001). Being fully vaccinated represented a significant protective factor (OR 0.12, 95% CI 0.04–0.35, p < 0.001). Conclusion: Older classes of age and a complete vaccination, in time with the recommended schedule, are both protective factors for hospitalisation in severe pertussis disease. The widespread vaccination delay frequently observed in preterm children may be the cause for their higher rate of hospitalisation.